Internal Audit Quality and Financial Reporting Quality: The Joint Importance of Independence and Competence - ABBOTT, LAWRENCE J.; DAUGHERTY, BRIAN; PARKER, SUSAN; PETERS, GARY F. (Journal of Accounting Research, 2016)
ABSTRACT In light of the growing importance of internal audit functions (IAF) and the limited archival evidence on internal audit quality, we examine an interactive model of IAF quality (comprised of competence and independence) to better understand the determinants of IAF effectiveness as a financial reporting monitor. Our tests support the hypothesis that the joint presence of competence and independence is a necessary antecedent to effective IAF financial reporting monitoring. In sum, our results show that, the answer to “what is the effect of internal audit competence (independence) on financial reporting quality?” is “it depends on the independence (competence) of the internal auditor.” Our study extends the understanding of IAF quality determinants in the realm of financial reporting as it relates to ongoing discussions by researchers, standard setters, regulators, and practitioners.